Topology Property Based on Network Tomography for Wireless Mobile Multihop Communication Network. (19th March 2014) - Qin, Danyang; Ma, Lin; Ding, Qun
The random movement of nodes makes the dynamic topology structure be one of the most important characteristics in wireless multihop communication network, which makes the description and quantization of the dynamic property the very foundation of the design, simulation, and measurement for this kind of network. The distributions of the link duration and the topology duration will be derived and verified by simulations. Then, the topology flapping sensing method has been put forward based on TTL. Finally, the probability model of the topology stability in the measurement time has been established and calculated based on network tomography for wireless mobile multihop communication network in this paper. Simulating results verify the correctness and efficiency of the approach, which will provide the technique basis of research on the dynamic property and end-to-end measurement for wireless mobile multihop communication network.